If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y = -2x + 8 Reorder the terms: 2y = 8 + -2x Solving 2y = 8 + -2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '2'. y = 4 + -1x Simplifying y = 4 + -1x
| 2x-11-2x=11 | | 5x-8x=-12-15 | | 8x-18=6y | | -16+8x=6(x-1) | | 4c-5c+6c= | | -3(x+7)=8-(2x+4) | | 8(3x)=132 | | -6(7+d)=-42whatsd | | 12(9c-1)-12=106c+12 | | 2*2*2-3*5*5*5*5*5= | | 4*3=25 | | -1.5(5x-9)=17 | | 56=-9x+56 | | 5x+18=8x-10 | | 12*+9-4*-4=3*-7-*+30 | | 15x^2+17x+4=0 | | 10*+9=59 | | Y+9=2 | | 5n-7(n+3)+2n=-25 | | 15=-2-5t | | c=rd+a | | -182=7(5x+4) | | 2l+4c=2.5 | | 1.5-x=-1.7 | | x=0.75+-0.25y | | -3(-4-6y)+7(-y+5)=0 | | y-3=6y+2 | | -77=-11a | | 4x+17=2x+23 | | 4x+17=2x+23 | | 4x+17=2x+23 | | (-3-4,-11+12)= |